The impact of media situation on people's memory effect – an ERP study. (March 2020) - Han, Ting; Xiu, Lichao; Yu, Guoming
Abstract: Using event-related potentials (ERPs) of memory, this study examines the impact of two media situations, cellphone situation (CS) and newspaper situation (NS). The objective of this study is to investigate and quantify the difference in human cognitive patterns in these two media situations. A recognition memory paradigm was adopted in this study. In a between-subject lab experiment the participants were instructed to carefully read a scientific article, and then to judge whether the words in the test phase had appeared in the article. The results show that there is no significant difference in overall accuracy and response time between the CS group and the NS group. Yet, the response time of participants is significantly different between new words and old words. The late positive component (LPC) results show the emergence of an old-new effect. This effect is more pronounced in the cellphone situation, especially in the 600–800 ms range. Participants in the mobile phone situation showed better memory than participants in the newspaper situation. These findings point to a detectable difference in cognition at the neurological level between different media situations. Highlights: There are differences in cognitive patterns between cellphone situation and newspaper situation. ERP late positive component (LPC) is enhanced in cellphone situation. The impact of media situation on the old-new effect occurs in the late processing stage, about 600–800 ms.